(untitled) (Revista horizonte, 2021)
The study has the purpose of designing and applying a didactic proposal for teaching sports games, based on the inclusion of perceptual and decisional aspects of the players, translated into sequences of individual tactical actions, in the defense and attack dimensions of the sports game. The methodology used considers two stages: first, an exposition and sanction of the individual-tactical sequences to an expert judgment. The second stage considered the experimental application of the sequences sanctioned in the previous stage, to a sample of athletes considered sports talents in the training stage (13-16 years), women and men, belonging to the disciplines of Soccer, Handball, and Hockey- roller skate. The results obtained show an increase in those game actions translated into an improvement of the game (anticipation, deterrence, efficient marking, efficient passing) in both dimensions (attack and defense), as well as a decrease in those actions of lower quality in the game (single pass, single dial).